2015
DOI: 10.1111/jocs.12576
|View full text |Cite
|
Sign up to set email alerts
|

Robot-Assisted Training Early After Cardiac Surgery

Abstract: Robot-assisted gait therapy with the Lokomat® system is feasible and safe in patients early after median sternotomy. Results with robot-assisted training were comparable to standard in hospital training. An adapted and combined aerobic and resistance training intervention with augmented feedback may result in benefits in walking distance and lower limb muscle strength (ClinicalTrials.gov number, NCT 02146196).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Furthermore, in patients with Parkinson's disease, no significant difference was found in the 6 min walking test and the 10 m walking test between RAG training and BWSTT [5]. The application of RAG training after cardiac surgery showed an advantage over general rehabilitation methods only in walking distance [9]. Thus, although RAG training has been applied in the treatment of various diseases, including cerebral palsy, Parkinson's disease, and myocardial infarction, most reports are case studies, and conclusive evidence concerning the therapeutic effects is inadequate [2].…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…Furthermore, in patients with Parkinson's disease, no significant difference was found in the 6 min walking test and the 10 m walking test between RAG training and BWSTT [5]. The application of RAG training after cardiac surgery showed an advantage over general rehabilitation methods only in walking distance [9]. Thus, although RAG training has been applied in the treatment of various diseases, including cerebral palsy, Parkinson's disease, and myocardial infarction, most reports are case studies, and conclusive evidence concerning the therapeutic effects is inadequate [2].…”
Section: Discussionmentioning
confidence: 80%
“…The RAG device is designed to induce the movements of patient's lower limbs according to pre-programmed normal gait patterns and is being applied in the treatment of patients with gait disturbance. The RAG device provides a more supportive environment and normalized physiological gait training with benefits of temporal aspects and ideal kinematics [2,[5][6][7][8][9][10][11][12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The group who developed Lokomat robotic system designed a study in order to assess feasibility and safety of a robot-assisted gait therapy in patients early after open heart surgery (16). They showed that the "results with robotassisted training were comparable to early postoperative standard in hospital training and no deep sternal wound infection or any adverse event occurred in the robot-assisted training group" (16). Thus, the robot-assisted gait therapy with the Lokomat system proved to be feasible and safe for postoperative cardiac rehabilitation.…”
Section: Discussionmentioning
confidence: 99%